Design and Fabrication of Shell Structures: Aided by Radial Basis Functions and Reconfigurable Mechanisms - Chiang, Yu-Chou (A+BE | Architecture and the Built Environment, 2022)
Shell structures carry loads with their thin yet curved shapes. Being thin means shells require little material, which is desirable for minimizing embodied carbon footprints. However, the feature of being curved implies shells require immense effort to design and fabricate. To address the challenges, this dissertation consists of three parts: developing a design algorithm based on radial basis functions (RBFs), inventing a fabrication technique based on reconfigurable mechanisms, and producing prototypes based on the new algorithm and mechanism. The first part of this dissertation introduces a new algorithm based on RBFs for designing smooth membrane shells, which is more versatile than existing methods. The algorithm can generate membranes with both tensile and compressive stresses. It can also tweak an initial shape to meet free-edge conditions. It can also incorporate horizontal loads in the form-finding process. The second part of the dissertation presents a new system of flat-to-curved mechanisms, which allows a shell to be fabricated in a flat configuration and deployed into a double-curved state. Such a mechanism consists of panels connected by tilted hinges. The mechanism can contract non-homogeneously and change its Gaussian curvature. The last part of this dissertation demonstrates the integral application of the RBFs form-finding algorithm and the flat-to-curved mechanisms. The prototypes designed and produced deliver form-found shapes that have spans ranging from 0.2 to 4 meters. This dissertation contributes to the development and distribution of shell structures by developing computer algorithms and digital fabrication techniques to minimize the hurdles of designing and fabricating shell structures.